Secondary Metabolites from Calophyllum soulattri and Calophyllum gracilentum and Their Antibacterial Activity - Dayang Nurul Anisa, Abang Heilman (Universiti Malaysia Sarawak, 2024)
Antibiotic resistance has emerged as a substantial threat to global public health, necessitating an urgent investigation and evaluation of novel antimicrobial agents to combat this escalating issue. Plants are valuable resources for the development of novel pharmaceutical products. Calophyllum species are known for having excellent biological activities such as antimicrobial and antiviral due to their secondary metabolites, which led to the selection of two Calophyllum species, Calophyllum soulattri and Calophyllum gracilentum for this study. The stem bark of C. soulattri and C. gracilentum were studied for their phytochemical and biological activities. The powdered stem bark of both Calophyllum species were extracted at room temperature sequentially with hexane, ethyl acetate and methanol. Each of the extracts were filtered and solvents removed by rotary evaporator to give hexane, ethyl acetate and methanol extracts. The extracts were isolated using various chromatography techniques such as column chromatography and thin layer chromatography which led to the isolation of a new xanthone, soulaxanthone (62), along with four other known metabolites, euxanthone (63), calopolyanolide E (19), calanolide E (3) and friedelin (60). The structures of these compounds were identified and elucidated using spectroscopic techniques such as MS, IR, 1D and 2D NMR. The extracts showed inhibition against Gram-negative bacteria but showed no inhibition against Gram-positive bacteria. For compounds, there were no inhibition demonstrated against B. cereus, L. plantarum and S. marcescens. Ethyl acetate extract of C. soulattri demonstrated moderate activity against P. aeruginosa (MIC = 125 µg/mL). Meanwhile, the hexane extract from both plants exhibited moderate activity against E. cloacae (MIC = 250 µg/mL). For isolated compound, soulaxanthone (62) exhibited moderate activity against P. aeruginosa with an MIC value of 25 µg/mL. Calopolyanolide E (19) and friedelin (60) demonstrated moderate activity against E. cloacae with the MIC values of 25 and 50 µg/mL, respectively. Both compounds showed bactericidal activity against E. cloacae with the similar value to ampicillin (MBC = 50 µg/mL). The significance of outcomes from this study is the isolation of a new xanthone, soulaxanthone from the stem bark of C. soulattri. For the future study, soulaxanthone could be isolated with higher percentage of yield by doing standardise method.